Transformación paisajística de la ronda hídrica, Quebrada Suratoque en el sector de campo Verde, Villa Lina y Palermo 1, del municipio Piedecuesta Santander (2021)
For the research of this project, an exploratory and descriptive technical analysis was conducted in the water roundabout of the Suratoque Creek in the Campo Verde sector, Villa Lina and Palermo 1, in the municipality of Piedecuesta Santander, through fiel d visits, photographic evidence and interviews with the community, which served as a starting point to know, identify and obtain a preliminary analysis of the problems and current situation of the water roundabout of the Suratoque Creek, This served as a s tarting point to know, identify and obtain a preliminary analysis of the problems and current situation of the Suratoque Creek in the municipality of Piedecuesta, Santander. Obtaining evidence of the problems such as the deterioration and lack of quality p ublic spaces, the scarcity and deterioration of urban equipment, insecurity and pollution, we propose the idea of developing a recreational, cultural and educational linear park along the Suratoque Creek, with the main objective of formulating an urban app roach to improve the spatial quality of the sector from transversal 2 to carrera cuarta, linking the body of water and the Suratoque Creek protection round.